Ecological footprints of food systems in South Asia - Urfels, Anton; Raghu, Prabhakaran T.; Chakraborty, Shreya; Shahrin, Sumona; Krupnik, Timothy J.; Mukherji, Aditi (International Maize and Wheat Improvement Center, 2022)
Food systems in South Asia exert considerable pressure on climate systems, water systems, and biodiversity. Quantifying these impacts and is crucial for steering food systems transitions. However, approaches and assessments for environmental footprints of food systems remain largely fragmented in South Asia, especially for low-income and data-scarce regions. We address this knowledge gap with systematic scoping review of peer-reviewed literature to identify existing methods and datasets applicable for assessing the environmental footprints and planetary boundaries of food systems in South Asia. We find that such assessments have started to become more common, although many remain narrowly focused on reliant on Tier 1 type of approaches. Others are singular case studies or describe experiments. For example, most studies look either at carbon and/or water footprints of national dietary or production patterns and their relationship to ecosystem functioning. We also find a concentration of studies on specific crops or food products in select ecological boundaries. We consequent suggest two avenues for future research: First, consolidating a meso-scale overview of environmental impacts of food systems exercises and strategy development. Second, research is needed to generate sub-regional diagnostic datasets. These could be helpful in developing context-specific, data-driven, and socially desirable solutions to address the most actionable environmental impacts of food systems in South Asia.